Human Resource Management in Strengthening Educators - Maslahatus Sariroh; Sri Minarti (Center for Studies in Advanced Science, 2025)
This research is the result of research that presents human resource management in strengthening educators at MAN 2 Kediri. The purpose of this study is to determine the planning, implementation, and evaluation of human resource management in strengthening educators in MAN 2 Kediri. The research method used is descriptive qualitative, which reveals facts, data, and phenomena that occur in the field. This research uses types of research in the form of field research and case study approaches. The results of this studyshow that: 1) Human resource management planning in strengthening educators in MAN 2 Kediri is planned with functionaries before entering the new school year and full authority is given to the head of the madrasah. The planning carried out at MAN 2 Kediri is in the form of MGMP, Workshops, and also Work Meetings. 2) The implementation of human resource management in strengthening educators in MAN 2 Kediri has been carried out by existing SOPs. Starting from MGMP, BIMTEK, and also work meetings. 3) Evaluation of human resource management in strengthening educators in MAN 2 Kediri using the PKG format.